2017
DOI: 10.1039/c6sm02107g
|View full text |Cite
|
Sign up to set email alerts
|

Protein diffusion in a bicontinuous microemulsion: inducing sub-diffusion by tuning the water domain size

Abstract: We study the diffusion of an enhanced green fluorescent protein (GFP+) in bicontinuous sugar-surfactant based microemulsions. The size of the water domains in such systems is controlled by changes of the oil-to-water ratio. Hence, microemulsions allow to produce confinement effects in a controlled way. At high water content the protein is found to exhibit Fickian diffusion. Decreasing the water domain size leads to a slowing down of the protein diffusion and sub-diffusive behavior is obtained on the scale obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…FCS is very well suited for microemulsion systems, as has been shown for W/O MEs, 108,109 bicontinuous MEs, 110 and O/W MEs, 111,112 allowing one to deduce size and size distribution of microemulsion droplets. 29 Since here only the motion of fluorescently labeled particles is measured, FCS also allows to measure the mobility of different fluorescently labeled compounds or additives of a microemulsion.…”
Section: Survey Of Techniques For Characterizing Microemulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…FCS is very well suited for microemulsion systems, as has been shown for W/O MEs, 108,109 bicontinuous MEs, 110 and O/W MEs, 111,112 allowing one to deduce size and size distribution of microemulsion droplets. 29 Since here only the motion of fluorescently labeled particles is measured, FCS also allows to measure the mobility of different fluorescently labeled compounds or additives of a microemulsion.…”
Section: Survey Of Techniques For Characterizing Microemulsionsmentioning
confidence: 99%
“…For bicontinuous microemulsions this method then enables one to determine the size of the water domains when using a probe like green fluorescent protein (GFP). 110 In addition, to FCS one can also employ the time-resolved decay of fluorescence to determine the aggregation number of droplet-type microemulsions. 113 Furthermore, fluorescence probes can be employed to characterize the local polarity within the domains of a microemulsion, 114 an aspect that can be particularly interesting when investigating microemulsions based on ionic liquids.…”
Section: Survey Of Techniques For Characterizing Microemulsionsmentioning
confidence: 99%
“…Although VE-BODIPY has a slightly higher molecular weight (747.86) than that of natural VE (430.79), these values are in good agreement with the results obtained with electrochemical measurements (Figure b). In contrast, Neubauer and co-workers were the first to investigate the diffusion of an enhanced green fluorescent protein (GFP+) in a BME (water/sugar surfactant + 1-pentanol/cyclohexane) estimated by FCS measurement . They reported that the GFP+ diffusion slowed as the water domain size in the BME decreased.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Neubauer and coworkers were the first to investigate the diffusion of an enhanced green fluorescent protein (GFP+) in a BME (water/ sugar surfactant + 1-pentanol/cyclohexane) estimated by FCS measurement. 41 They reported that the GFP+ diffusion slowed as the water domain size in the BME decreased. Very interestingly, our study (lipophilic VE diffusion through the micro-oil phase in a BME) was conceptually opposite to their study (hydrophilic GFP+ diffusion through the micro-water phase in a BME), but the tendency of the diffusion of each species in the BME was the same.…”
Section: T H Imentioning
confidence: 99%
“…Neubauer and co-workers were the first to use FCS measurement to investigate the diffusion of an enhanced green fluorescent protein (GFP+) in a BME (water/sugar surfactant+1-pentanol/cyclohexane). 25 They reported that the GFP+ diffusion slowed as the water domain size in the BME decreased.…”
Section: Fcs Measurementsmentioning
confidence: 99%